2003
DOI: 10.2320/matertrans.44.713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Frequency on High-Temperature Fatigue Behavior of 17-4 PH Stainless Steels

Abstract: The effect of frequency (2 and 20 Hz) on the high-cycle fatigue and fracture behavior was investigated at 573-773 K for 17-4 PH stainless steels in three conditions: Condition A (unaged), H900 (peak-aged) and H1150 (overaged). S-N results indicated that at 573 and 673 K, there was generally no difference in fatigue strength between 2 and 20 Hz, except for H900 at 673 K where the fatigue strength at 2 Hz was lower than that at 20 Hz. At 773 K, the fatigue strength of each condition at 2 Hz was lower than that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Apparently, thermal activation of dislocations became more operative than the hardening DSA effect for the given alloys tested at 500 • C resulting in cyclic soft- ening. Moreover, the authors' previous investigations [6,7] indicated that coarsening of Cu-rich phases was observed in Conditions A and H900 tested at 500 • C and resulted in a reduction of hardness and fatigue resistance. Consequently, in addition to dynamic dislocation recovery, the coarsening of Cu-rich precipitates is believed to contribute to cyclic softening in Conditions A and H900 at 500 • C. Furthermore, due to an increase in the period of a cycle with decreasing strain rate, the coarsening effect would become more effective such that the stress level was significantly decreased with a reduction in strain rate for Conditions A and H900 tested at 500 • C. Fig.…”
Section: Cyclic Stress Responsementioning
confidence: 94%
See 1 more Smart Citation
“…Apparently, thermal activation of dislocations became more operative than the hardening DSA effect for the given alloys tested at 500 • C resulting in cyclic soft- ening. Moreover, the authors' previous investigations [6,7] indicated that coarsening of Cu-rich phases was observed in Conditions A and H900 tested at 500 • C and resulted in a reduction of hardness and fatigue resistance. Consequently, in addition to dynamic dislocation recovery, the coarsening of Cu-rich precipitates is believed to contribute to cyclic softening in Conditions A and H900 at 500 • C. Furthermore, due to an increase in the period of a cycle with decreasing strain rate, the coarsening effect would become more effective such that the stress level was significantly decreased with a reduction in strain rate for Conditions A and H900 tested at 500 • C. Fig.…”
Section: Cyclic Stress Responsementioning
confidence: 94%
“…As part of a series of studies on the high-temperature mechanical and fatigue properties of 17-4 PH stainless steels [5][6][7], the objective of the present study is to characterize the LCF behavior of such materials at high temperatures. In this study, systematic experiments were conducted to investigate the influence of strain rate (10 −2 , 10 −3 and 10 −4 s −1 ) on LCF life, cyclic stress response (CSR), and dislocation substructure at 300-500 • C for variously heat-treated 17-4 PH stainless steels.…”
Section: Introductionmentioning
confidence: 99%
“…Although a limited number of studies on the high-temperature characteristics of 17-4 PH alloy have been reported [8,[13][14][15][16], the high-temperature FCG behavior of this alloy has not been reported yet. As part of a series of studies on the high-temperature fatigue properties of 17-4 PH stainless steel [14][15][16], the objective of this study is therefore to characterize the high-temperature FCG behavior of variously heat-treated 17-4 PH stainless steels by conducting systematic experiments at room temperature (RT), 300, 400, and 500 o C. Mo, 0.03 S, 0.02 C, 0.016 P and Fe (balance). Three different types of heat treatments were applied, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Since engineering structures often contain flaws or crack-like defects, a study on the fatigue crack growth (FCG) behavior of 17-4 PH stainless steel at high temperatures is of great importance for the design and life prediction of its various applications. Although there are a few investigations focused on the high-temperature characteristics of 17-4 PH stainless steel, 7,[12][13][14][15][16][17] study on the high-temperature FCG behavior is very limited 17) and lacks consideration of the frequency effect. Frequency is an important factor governing FCG behavior at high temperatures because time-dependent mechanisms, such as creep and oxidation, may take place during fatigue loading.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a series of studies on the high-temperature fatigue and mechanical properties of 17-4 PH stainless steel, [13][14][15][16][17] the aim of this study is to characterize the influence of loading frequency on the high-temperature FCG behavior of variously heat-treated 17-4 PH stainless steels by conducting systematic experiments at 673 and 773 K.…”
Section: Introductionmentioning
confidence: 99%